International evidence-based medicine survey of the veterinary profession: information sources used by veterinarians - Huntley, Selene J.; Dean, Rachel S.; Massey, Andrew; Brennan, Marnie L. (Public Library of Science, 2016)
Veterinarians are encouraged to use evidence to inform their practice, but it is unknown what resources (e.g. journals, electronic sources) are accessed by them globally. Understanding the key places veterinarians seek information can inform where new clinically relevant evidence should most effectively be placed. An international survey was conducted to gain understanding of how veterinary information is accessed by veterinarians worldwide. There were 2137 useable responses to the questionnaire from veterinarians in 78 countries. The majority of respondents (n = 1835/2137, 85.9%) undertook clinical work and worked in a high income country (n = 1576/1762, 89.4%). Respondents heard about the survey via national veterinary organisations or regulatory bodies (31.5%), online veterinary forums and websites (22.7%), regional, discipline-based or international veterinary organisations (22.7%) or by direct invitation from the researchers or via friends, colleagues or social media (7.6%). Clinicians and non-clinicians reportedly used journals most commonly (65.8%, n = 1207/1835; 75.6%, n = 216/286) followed by electronic resources (58.7%, n = 1077/1835; 55.9%, n = 160/286), respectively. Respondents listed a total of 518 journals and 567 electronic sources that they read. Differences in veterinarian preference for resources in developed, and developing countries, were found. The nominated journals most read were the Journal of the American Veterinary Medical Association (12.7% of nominations) for clinicians and the Veterinary Record (5.7%) for non-clinicians. The most accessed electronic resource reported was the Veterinary Information Network (25.6%) for clinicians and PubMed (7.4%) for non-clinicians. In conclusion, a wide array of journals and electronic resources appear to be accessed by veterinarians worldwide. Veterinary organisations appear to play an important role in global communication and outreach to veterinarians and consideration should be given to how these channels could be best utilised for effective dissemination of key research findings.